1985
DOI: 10.1210/endo-116-4-1253
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hyperthyroidism on Experimental Autoimmune Thyroiditis in the Rat*

Abstract: The effects of hyperthyroidism on experimental autoimmune thyroiditis were investigated in the rat. Rats were given T4 twice daily by sc injection in amounts sufficient to raise circulating hormone levels 10-fold 4 h after administration. Thyroiditis was induced by immunization with rat thyroglobulin (Tg) in complete Freund's adjuvant, and the severity of the disease was assessed by comparison with saline-treated controls. Thymic and splenic hypertrophy were found in T4-treated animals, whereas lymph node wt d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
4

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 20 publications
0
23
0
4
Order By: Relevance
“…27 Furthermore, there are reports that show that thyroid hormones either had no effect on humoral immunity 28 or suppressed it. 29 One report demonstrated elevation of antibody response with anti-thyroid drug treatment. 30 The results of the present study regarding hypergammablobulinemia in hyperythyroid group are consistent with results reported recently by Nandakumar et al 31 The hypergammablobulinemia in hyperythyroid patients has been associated with the activation of NF-kB in B lymphocytes through oxidative stress induced by thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…27 Furthermore, there are reports that show that thyroid hormones either had no effect on humoral immunity 28 or suppressed it. 29 One report demonstrated elevation of antibody response with anti-thyroid drug treatment. 30 The results of the present study regarding hypergammablobulinemia in hyperythyroid group are consistent with results reported recently by Nandakumar et al 31 The hypergammablobulinemia in hyperythyroid patients has been associated with the activation of NF-kB in B lymphocytes through oxidative stress induced by thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…It is not yet known how the degree of tissue destruction correlates to the clinical and biochemical disease manifestations. We did not measure anti-Tg antibodies in these rats but previous studies have found that the presence and the level of anti-Tg antibodies correlate with the presence of AIT in both spontaneous and induced rat models of AIT also after T 4 treatment (16,18,28,45,46) although one study found no difference after T 4 treatment (27) and another study could not find a correlation between the degree of AIT and the level of anti-Tg antibodies after induction of AIT by iodinated Tg (21).…”
Section: Body Weight (G) (Mean^sem) (N)mentioning
confidence: 89%
“…In keeping with our study, the preventive effect of T 3 on the incidence of thyroiditis has been described in previous studies in spontaneous and induced AIT in rats (26 -28) and hypothyroid cats (29) where the incidence, severity and level of antibodies were found to be reduced after treatment with T 4 . In these previous studies, T 4 and not T 3 was used and it was administered in supraphysiological doses and for periods of up to 3 months (26)(27)(28). Only in one previous study was no effect of T 4 on the prevalence of AIT found (30).…”
Section: Body Weight (G) (Mean^sem) (N)mentioning
confidence: 99%
“…One group has reported that the proportions of splenic and blood T cells do not change in rats treated with triiodothyronine or PTU for 17 days [14], but another group reports that the proportion of blood T cells decreases in hyperthyroxinemic rats treated with T4 for 5 weeks [18]. Our results show that hyperand hypothyroxinemia for 8 weeks did not change the proportions and numbers of T and B cells in the spleen or thymus, and that only hyperthyroxinemia for 8 weeks increased the proportion and number of NK cells in the spleen.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports of immunological changes in experimental hyperand hypothyroxinemic animals [10][11][12][13][14][15][16][17][18][19][20], but only few and conflicting reports on the enumeration of lymphocyte subsets [14,18]. However, these findings were obtained from studies of the effects of hyperand hypothyroxinemia that lasted less than 2 months (8 weeks); there is no report on the longterm effect of hyper-and hypothyroxinemia that lasted more than 6 months (32 weeks).…”
Section: Changesmentioning
confidence: 99%